Species Composition and Stand Structure in Logged Over Area in Forest Concession of PT Salaki Summa Sejahtera, Province of West Sumatra - Iwan Hilwan (Jurnal Silvikultur Tropika, 2012)
Production forest in Sumatra, Kalimantan, and other islands, are located in lowland tropical rain forest, where in this forest type were dominated by plant species of Dipterocarpaceae. Many tree per hectar was cut to produce major commercial timber.  This timber harvesting activity with selective cutting method (TPTI sylviculture system) can rise impact to species composition and stand structure in logged over area (LOA).  Because that condition, study on species composition and stand structure in primary forest or virgin forest and logged over area is very important to provide data and information for forest management. According vegetation analysis in 1 ha sample plot at virgin forest and logged over forest, species composition and stand structure in logged over area is not significantly different. This condition indicate that implemented of TPTI was not change to species composition and stand structure in logged over area. Species dominant and co-dominant at virgin forest and logged over forest are similar, which are species trees of Shorea (meranti) and Dipterocarpus (keruing). Stand structure at virgin forest and logged over forest are not different, they have J-reverse curve as characteristic of uneven-aged natural forest.